A performance comparison of specialised (industrial) and non-specialised real estate investment trusts in South Africa - Makatsane, Ntseno P. (Department of Construction Economics and Management, 2019)
There is a belief that anything that is specialised tends to outperform the diversified counterparts and this study investigates if this proposition applies in the property industry, specifically the REIT (Real Estate Investment Trust) market in South Africa (SA). The norm is to apply a quantitative methodology when assessing performance but this study follows a qualitative approach in comparing the overall performance between specialised and diversified REITs in SA using non-quantitative metrics. A mix of specialised and diversified REITs in SA were sampled and a multiple case study analysis was done after interviewing senior management in four REITs. A total of four interviews were done with five respondents across four cases. These cases were then analysed using thematic analysis. The respondents were asked questions relating to the REIT they are working for, industrial specialised and diversified REITs performance and the SA property market as a whole. The overall findings suggest that diversified REITs may outperform the specialised REITs in SA currently however, this conclusion depends on a lot of factors. These factors include the analysis time of reference, the economic status of the country (for example, recession), the size of the REIT, the company gearing level, how that specific sector is performing at that particular time relative to others and the management efficiency level. The growth of e-commerce plays a vital role as a factor as well because it is said to be replacing the brick and mortar retail industry therefore, its influence affects the specialised industrial sector performance. For further research, a similar study with a quantitative approach can be considered in order to add to the SA REIT body of knowledge. Furthermore, research on the performance of property companies before and after attaining REIT status could be investigated to determine the REIT status effect on the company. To add on to the SA REIT literature, performance between REITs in different sectors and provinces could be explored.